Effect of Nitrogen Fertilization on Biomass Yield and Chemical Composition of German Grass (South Asian Journal of Agriculture, 2025)
The aim of the experiment was to evaluate the effect of N fertilizer in the form of urea on the biomass yield and nutritional value of German grass (Echinochloa polystachya). A randomized complete block design (RCBD) with three replications was used to design the experiment. Nitrogen fertilizer treatments were 130, 140, 150 and 160 kg ha-1N with control. Doses of other fertilizers such as TSP, MoP, gypsum and zinc sulphate were kept constant for all treatments. The first and second cuttings were done at 60 and 90 days after planting (DAP), respectively. Data on selected parameters of biomass yield and nutrient composition were collected and analyzed on computer using SAS version 9.1. The results revealed that biomass yield of German grass increased with increasing N fertilizer dose at 60 DAP with highest at N dose of 160 kg ha-1 (52.78±2.82 t ha-1) and lowest in control (32.11±1.64t ha-1) (p≤0.01). Biomass yield increased numerically (p≥0.05) with increasing N fertilizer dose at 90 DAP. Crude protein (CP) percentage of German grass increased with increasing N fertilization and the highest value was observed with N dose of 160 t ha-1 for both cuttings at 60 DAP (10.52±0.04; p≤0.001) and 90 DAP (11.30±0.25; p≤0.05). Dry matter (DM), crude fiber (CF), ether extract (EE) and ash percentage of German grass did not vary significantly for both cuttings (p>0.05). It can be concluded that biomass yield and CP content were significantly improved by application of 160 kg ha-1 N fertilizer.  South Asian J. Agric., Vol. 10, No.1-2, 2024: 47-53